2022
DOI: 10.1021/acs.jpca.2c04373
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Confirmation of H2O2 Adsorption at the Water–Air Interface

Abstract: Recent work has reported that hydrogen peroxide is formed at the air−water interface. Given the reduced solvation environment there, this process could give rise to enhanced production of OH from H 2 O 2 photolysis at the interface. These considerations give some importance to understanding the adsorption thermochemistry of hydrogen peroxide. Although there are two molecular dynamics studies that provide the adsorption free energy, to date there is no experimental verification that H 2 O 2 adsorbs at the air−w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
(77 reference statements)
2
8
0
Order By: Relevance
“…Hence, the only possibility that could explain the spontaneous H 2 O 2 formation from water droplets is the Gibbs free energies of H 2 O 2 and H 2 decrease when moving from bulk to the interface (Figure b). H 2 O 2 is energetically −1.2 kcal/mol more favorable at the air–water interface (as compared to its free energy in liquid water) as measured recently by glancing-angle Raman spectroscopy . MD simulations showed that H 2 O 2 and other small molecule gases such as N 2 and O 2 are about −1 kcal/mol more favorable at the air–water interface than in water .…”
Section: Moving Forward: Some Potential New Approachessupporting
confidence: 51%
See 2 more Smart Citations
“…Hence, the only possibility that could explain the spontaneous H 2 O 2 formation from water droplets is the Gibbs free energies of H 2 O 2 and H 2 decrease when moving from bulk to the interface (Figure b). H 2 O 2 is energetically −1.2 kcal/mol more favorable at the air–water interface (as compared to its free energy in liquid water) as measured recently by glancing-angle Raman spectroscopy . MD simulations showed that H 2 O 2 and other small molecule gases such as N 2 and O 2 are about −1 kcal/mol more favorable at the air–water interface than in water .…”
Section: Moving Forward: Some Potential New Approachessupporting
confidence: 51%
“…Some interface-sensitive spectroscopies, such as sum-frequency generation (SFG), can potentially probe intermediates or H 2 O 2 product at water droplet surfaces. Recent glancing-angle Raman spectroscopy on 1 M H 2 O 2 solution confirmed the surface propensity of H 2 O 2 at the water–air interface with the standard free energy adsorption of −1.2 kcal/mol . This adsorption energy had also been predicted by molecular dynamics (MD) simulations. , However, low concentrations of these species could be a challenge for detection.…”
Section: Moving Forward: Some Potential New Approachesmentioning
confidence: 84%
See 1 more Smart Citation
“…Relative to the air–water interface, the H 2 O 2 molecule in bulk water was approximately 0.7 kcal/mol higher. Our calculations are consistent with recent experimental results confirming the enrichment of H 2 O 2 molecules at the air–water interface.…”
Section: Resultssupporting
confidence: 92%
“…Reactions on surfaces are examined, including a kinetic and mechanistic study of gas–solid and gas-phase ozonolysis of nitrogen-containing alkenes, and the formation of organic nitrates in the heterogeneous reaction of α-pinene with mineral surfaces . Laboratory studies of the air–water interface demonstrate surface adsorption of H 2 O 2 , as well as determining the structure of hydroxy organic acids of varying size at the interface . Additional work addresses adsorption–desorption of semivolatile VOCs on mineral surfaces, and reactive uptake of HgO and a recently discovered dimethyl sulfide oxidation product (hydroperoxymethyl thioformate) on aerosols of various compositions. , The effects of aerosol properties on ice nucleation and on the partitioning of semivolatiles, , the effects of pH on organosulfate structures in the condensed phase, and the accessibility of various nanostructures for surfactants on atmospheric aerosol proxies are also reported.…”
mentioning
confidence: 99%